A C(π-hole)⋯Cl–Zn tetrel interaction driving a metal–organic supramolecular assembly. Issue 42 (22nd October 2020) - Ramírez de Arellano, Carmen; Adam, Rosa; Ballesteros-Garrido, Rafael; Abarca, Belen; Ballesteros, Rafael; Alcorta, Ibon; Elguero, José; Escrivà, Emilio
Abstract : A brominated pyrimidinyl triazolopyridine ligand (bptpy) forms a C(π-hole)⋯Cl–Zn tetrel interaction that drives the formation of supramolecular layers through chain assembly in 18 membered metallacycle [(ZnCl2 )2 (μ-bptpy)2 ] crystals. Abstract : A brominated pyrimidinyl triazolopyridine ligand (bptpy) forms a C(π-hole)⋯Cl–Zn tetrel interaction that plays a determining role in the formation of supramolecular layers through chain assembly in 18 membered metallacycle [(ZnCl2 )2 (μ-bptpy)2 ] crystals. Supramolecular chains are formed through C–H⋯X interactions. The observed interactions are supported by DFT calculations using model dimers.